Determinants of Employee Performance in Nepalese Commercial Banks - K.C., Simran (Nepalese Journal of Economics, 2025)
This study examines determinants of employee performance in Nepalese commercial banks. Employee performance is selected as the dependent variable. Similarly, supervisor relationship, incentives & rewards, career development, organization culture, knowledge & skills, and self-motivation are selected as the independent variables. This study is based on primary data with 119 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance different factors influencing employee performance in Nepalese commercial banks. The study showed that supervisor relationship has a positive impact on employee performance. It means that better supervisor relationship leads to better employee performance. Similarly, incentives & rewards, has a positive impact on employee performance. It indicates that increase in incentives & rewards leads to increase in employee performance. Moreover, career development has a positive impact on employee performance. It means that increase in career development leads to increase in employee performance. Likewise, organization culture has a positive impact on employee performance. It shows that better organization culture leads to better employee performance. Similarly, knowledge & skills has positive impact on employee performance. It shows that higher the knowledge & skills, higher would be the employee performance. Further, self-motivation has a positive impact on employee performance. It shows that higher the self-motivation, higher would be the employee performance.